2006
DOI: 10.1158/1078-0432.ccr-05-2137
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Immuno–Positron Emission Tomography with Zirconium-89-Labeled Chimeric Monoclonal Antibody U36 in the Detection of Lymph Node Metastases in Head and Neck Cancer Patients

Abstract: Purpose: Immuno^positron emission tomography (PET), the combination of PET with monoclonal antibodies (mAb), is an attractive option to improve tumor detection and to guide mAb-based therapy. The long-lived positron emitter zirconium-89 ( 89 Zr) has ideal physical characteristics for immuno-PET with intact mAbs but has never been used in a clinical setting. In the present feasibility study, we aimed to evaluate the diagnostic imaging performance of immuno-PET with 89 Zr-labeled-chimeric mAb (cmAb) U36 in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
184
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 208 publications
(193 citation statements)
references
References 15 publications
2
184
1
Order By: Relevance
“…It is already proven with numerous antibodies (39,(70)(71)(72)(73)(74) and other proteins (75,76) through the efforts of groups in The Netherlands where it has been developed in both preclinical and, with good manufacturing practices (GMP) production for tracer production and validation, in clinical settings. Although Zr-89 does have an extraneous high-energy gamma ray (909 keV), the image quality is good and the overall radiation burden is well tolerated (77).…”
Section: The Advent Of Zirconium-89mentioning
confidence: 99%
“…It is already proven with numerous antibodies (39,(70)(71)(72)(73)(74) and other proteins (75,76) through the efforts of groups in The Netherlands where it has been developed in both preclinical and, with good manufacturing practices (GMP) production for tracer production and validation, in clinical settings. Although Zr-89 does have an extraneous high-energy gamma ray (909 keV), the image quality is good and the overall radiation burden is well tolerated (77).…”
Section: The Advent Of Zirconium-89mentioning
confidence: 99%
“…This in turn might indicate a promising role in treatment of hematological malignancies. Besides of the therapeutic effect also diagnostic use of CD44v6 antibodies is shown by successful detection of HNSCC lymph node metastases via immuno-PET by 89 ZrcmAb U36 [139,138].…”
Section: Experimental Antagonization and Drug Resistancementioning
confidence: 99%
“…86 Zr is attractive in terms of its long half-life and good spatial imaging, but has a potential problem with a 909 keV gamma emission. Appropriate BFCs for this metal ion have only recently been desctibed (11). 64 Cu was chosen for the studies reported here based on its wide availability, good spatial resolution, and relatively short half-life, limiting its potential imaging dose to patients.…”
Section: Abstract Carcinoembryonic Antigen; Bifunctional Chelate; Radmentioning
confidence: 99%